Proposed geoheritage sites along the transects of the Lunavada and surrounding areas promoting sustainable tourism within NE Gujarat and SW Rajasthan, India - Aditya U. Joshi; Gayatri Akolkar; Parita Gorania; Manoj A. Limaye; Bhushan S. Deota; Kaushik Baruah; Joshua Godinho; Muhammed Khaliz; Sakshi V. Samji; Tirthrajsinh Solanki; Pushprajsinh Solanki; Gaurav Chauhan (Geoheritage, 2025)

Identification and expression analysis of long non-coding RNAs of rice induced during interaction with Rhizoctonia solani - P. Supriya; G.K. Srividya; Manish Solanki; D. Manvitha; V. Prakasam; M. Balakrishnan; C.N. Neeraja; Ch Srinivasa Rao; R.M. Sundaram; Satendra K. Mangrauthia (Physiological and Molecular Plant Pathology, 2024)

Reuse of poor-quality water for sustainable crop production in the changing scenario of climate - M. L. Dotaniya; V. D. Meena; J. K. Saha; C. K. Dotaniya; Alaa El Din Mahmoud; B. L. Meena; M. D. Meena; R. C. Sanwal; Ram Swaroop Meena; R. K. Doutaniya; Praveen Solanki; Manju Lata; et al. (Environment, Development and Sustainability, 2023)

Development of a novel method for multiple phytohormone analysis by UHPLC-MS/MS from bio-enriched organic fertilizer prepared using banana pseudostem sap waste - Harihar Vaidya; Vanrajsinh H. Solanki; Rohan V. Kansara; Chirag Desai; Susheel Singh; Jayesh Patel; Trupti K. Vyas; Hiren Patel (Environmental Science and Pollution Research, 2022)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

In vitro regeneration through indirect organogenesis, genetic uniformity analysis and mineral content determination of finger millet (Eleusine coracana L.) - Rohan V. Kansara; Vanrajsinh H. Solanki; Vishal S. Srivashtav; Ramesh M. Patel; Kelvin D. Gandhi; Vivek S. Mehta (Biologia, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Feasibility of combining functional near-infrared spectroscopy with electroencephalography to identify chronic stroke responders to cerebellar transcranial direct current stimulation—a computational modeling and portable neuroimaging methodological study - Zeynab Rezaee; Shashi Ranjan; Dhaval Solanki; Mahasweta Bhattacharya; M. V. Padma Srivastava; Uttama Lahiri; Anirban Dutta (The Cerebellum, 2021)

Insights into the rust resistance base of common wheat (Triticum aestivum L.) in India - A. N. Mishra; K. N. Tiwari; Vaibhav K. Singh; M. Sivasamy; Dharam Pal; S. C. Bhardwaj; O. P. Gangwar; T. L. Prakasha; K. S. Solanki; Rahul M. Phuke; S. V. Sai Prasad; C. N. Mishra; et al. (Indian Phytopathology, 2021)

Inheritance of leaf rust resistance in four popular Indian durum wheat cultivars - A. Divya; T. L. Prakasha; A. N. Mishra; S. Chand; K. S. Solanki; Pramod Prasad; S. V. Sai Prasad (Indian Phytopathology, 2020)

Impact of atmospheric conditions in surface–air exchange of energy in a topographically complex terrain over Umiam - Nilamoni Barman; Arup Borgohain; S. S. Kundu; Biswajit Saha; Rakesh Roy; Raman Solanki; N. V. P. Kiran Kumar; P. L. N Raju (Meteorology and Atmospheric Physics, 2019)

Daytime Temporal Variation of Surface-Layer Parameters and Turbulence Kinetic Energy Budget in Topographically Complex Terrain Around Umiam, India - Nilamoni Barman; Arup Borgohain; S. S. Kundu; Rakesh Roy; Biswajit Saha; Raman Solanki; N. V. P. Kiran Kumar; P. L. N. Raju (Boundary-Layer Meteorology, 2019)

Impact of Mountainous Topography on Surface-Layer Parameters During Weak Mean-Flow Conditions - Raman Solanki; Narendra Singh; N. V. P. Kiran Kumar; K. Rajeev; Ryoichi Imasu; S. K. Dhaka (Boundary-Layer Meteorology, 2019)

Crop establishment with conservation tillage and crop residue retention in rice-based cropping systems of Eastern India: yield advantage and economic benefit - Rajiv Nandan; S. S. Singh; V. Kumar; V. Singh; K. K. Hazra; C. P. Nath; R. K. Malik; S. P. Poonia; Ch. Hemant Solanki (Paddy and Water Environment, 2018)

Time Variability of Surface-Layer Characteristics over a Mountain Ridge in the Central Himalayas During the Spring Season - Raman Solanki; Narendra Singh; N. V. P. Kiran Kumar; K. Rajeev; S. K. Dhaka (Boundary-Layer Meteorology, 2016)

Obesity shifts house dust mite-induced airway cellular infiltration from eosinophils to macrophages: effects of glucocorticoid treatment - J. Diaz; L. Warren; L. Helfner; X. Xue; P. K. Chatterjee; M. Gupta; M. H. Solanki; M. Esposito; V. Bonagura; C. N. Metz (Immunologic Research, 2015)

H19 gene methylation study in Indian buffalo (Bubalus bubalis) - Ajai K. Tripathi; Jitendra V. Solanki; Chaitanya G. Joshi (Veterinary Research Communications, 2013)

Synergistic application of oceanographic variables from multi-satellite sensors for forecasting potential fishing zones: methodology and validation results - H. U. Solanki; Prince Prakash; R. M. Dwivedi; Shailesh Nayak; Arvind Kulkarni; V. S. Somvamshi (International Journal of Remote Sensing, 2010)

Composite image of chlorophyll and sea surface temperature (SST) using MODIS-AQUA - Prakash Chauhan; P. V. Nagamani; H. U. Solanki; Shailesh Nayak (Journal of the Indian Society of Remote Sensing, 2005)

Potential fishing zones (PFZ) forecast using satellite data derived biological and physical processes - H. U. Solanki; R. M. Dwivedi; Shailesh Nayak; D. K. Gulati; M. E. John; V. S. Somvanshi (Journal of the Indian Society of Remote Sensing, 2003)